Memahami Penerimaan Diri pada Pengidap HIV Melalui Talkshow - Dewi, Lharasati; Indriani, Dewi; Kumala Dewi, Dinda; Puji Lestari, Marsela; Atussolihah, Mar; Saputra, Aditya (Jurnal Pengabdian Pada Masyarakat METHABDI, 2025)
The stigma and psychological burden experienced by people living with HIV/AIDS (PLWHA) often hinder their self-acceptance process. This community service activity aimed to support self-acceptance among young men living with HIV in Samarinda through an interactive talk show. The program involved 15 participants aged 18–25 years from the Mahakam Plus Community and featured two professional speakers who discussed gratitude strategies and the role of family support. Activities included material presentations, group discussions, relaxation exercises, and reflective practices such as gratitude journaling and a "tree of hope" activity. The results showed a positive response from participants, with increased openness during discussions and improved emotional awareness through reflective practices. These findings suggest that a community-based intervention combining education, reflection, and interactive activities can effectively enhance self-acceptance and psychological well-being among PLWHA.